Magnetocaloric Materials with Multiple Instabilities. Issue 25 (7th April 2017) - Taguchi, Yasujiro; Sakai, Hideaki; Choudhury, Debraj
Abstract : The magnetocaloric effect is a well‐known phenomenon where the temperature of a magnetic material varies upon application or removal of a magnetic field. This effect is anticipated to be applied to magnetic refrigeration technology, which is environmentally benign. For practical applications, it is essential to explore and expand the materials horizon of novel magnets that exhibit giant magnetocaloric effects to achieve sufficient cooling efficiency. In this article, several attempts to enhance the magnetocaloric effect are reviewed from the viewpoint of the competition or cooperation between the ferromagnetic interaction and other magnetic, electronic, and structural instabilities in strongly correlated materials. The results indicate that both the competition and cooperation between them promote the first‐order nature of the magnetic transition, leading to giant magnetocaloric effects. Therefore, exploiting multiple instabilities is a promising strategy for exploring new magnetocaloric materials. Abstract : The magnetocaloric effect is a phenomenon where the temperature of a magnetic material varies upon application or removal of a magnetic field. Several attempts to enhance the magnetocaloric effect are reviewed from the viewpoint of the competition or cooperation between the ferromagnetic interaction and other magnetic, electronic, and structural instabilities in strongly correlated materials.